Qualitative and physiological properties of 'Pompia', a citron-like fruit - Fronteddu, F.=700 1 Usai, M.; Palma, A.
(En, Fr, Es)
ilus., 14 ref.
Keywords: CITRUS; FISIOLOGIA VEGETAL; FRUTO; PROPIEDADES ORGANOLEPTICAS; RESPIRACION; ETILENO; ITALIA